Benzenedithiolate-bridged MoFe complexes: structures, oxidation states, and reactivities. Issue 26 (22nd June 2020) - Tsukada, Satoru; Abe, Takayuki; Abe, Naoya; Nakashima, Satoru; Yamamoto, Kazuki; Gunji, Takahiro
Abstract : The benzenedithiolate-bridged MoFe complexes were synthesized and the oxidation states of the metal centers elucidated. Abstract : Two benzendithiolate-bridged MoFe complexes, [(Me3 P)2 (CO)2 Mo(μ-S2 C6 H4 )Fe(CO)3 ] (1 ) and [(Me3 P)(CO)3 Mo(μ-S2 C6 H4 )Fe(CO)3 ] (2 ), were synthesized by reacting [Mo(S2 C6 H4 )(CO)2 (PMe3 )2 ] (3 ) with Fe(CO)5 . Each complex has a direct Mo–Fe bond that is supported by a bridging benzenedithiolate ligand and a semi-bridging carbonyl ligand as elucidated by single-crystal X-ray diffractometry. The structural data and differences in reactivity of these complexes suggest that monophosphine complex 2 is formed via diphosphine complex 1 . The reaction of 2 with PMe3 gives the diiron bis(dithiolate) complex, [Fe(S2 C6 H4 )(CO)2 (PMe3 )]2 (4 ), rather than 1 . 57 Fe Mössbauer and X-ray photoelectron spectroscopy studies reveal the oxidation states of the metal centers in 2 to be Fe 0 and Mo II .